2019
DOI: 10.1002/mawe.201700062
|View full text |Cite
|
Sign up to set email alerts
|

Wear and corrosion studies of graphite‐aluminum composite reinforced with micro/nano‐TiB2 via spark plasma sintering

Abstract: The demand for lightweight materials in the automobile and aerospace industries has led to various researches on graphite and graphite‐aluminum composites. The aim of this study was to investigate the effect of the addition of micron/nano TiB2 particles on the properties of graphite‐aluminum composite particularly the wear resistance. The powders were sintered at 550 °C and 50 MPa with more attention on the effect of the sintering temperature on densification, microhardness, coefficient of thermal expansion, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Other researchers had confirmed that the higher the reinforcement content, the higher the probability of clusters Research Article SN Applied Sciences (2020) 2:2109 | https://doi.org/10.1007/s42452-020-03960-z and particle defects and consequently, the reduction in the composite densification and hence, in its density [8,27].…”
Section: Displacement Rate As a Function Of The Temperature Of The Admentioning
confidence: 99%
See 3 more Smart Citations
“…Other researchers had confirmed that the higher the reinforcement content, the higher the probability of clusters Research Article SN Applied Sciences (2020) 2:2109 | https://doi.org/10.1007/s42452-020-03960-z and particle defects and consequently, the reduction in the composite densification and hence, in its density [8,27].…”
Section: Displacement Rate As a Function Of The Temperature Of The Admentioning
confidence: 99%
“…However, the extinction of the peaks in this study, which are responsible for the proper densifications, according to the work of Diouf and Molinari [25], could be attributed to the presence of dissolved oxygen in the samples, as can be seen in the SEM and EDS images (Figs. 5,6,7,8,9,10). The presence of oxygen in the sintering samples, during the spark plasma sintering process, hinders the densification mechanism [26].…”
Section: Displacement Rate As a Function Of The Temperature Of The Admentioning
confidence: 99%
See 2 more Smart Citations
“…This combination of high specific properties makes AMCs interesting for structural elements in the transport industry . Moreover, ceramic particles commonly employed as reinforcement such as silicon carbide (SiC) or titanium diboride (TiB 2 ) present high strength, stiffness, and excellent fatigue and wear resistance . These mechanical properties can also be improved by a decrease of reinforcement size, from micrometric to nanometric size .…”
Section: Introductionmentioning
confidence: 99%